Default in Payment in Land Sales That Have Been Registered at the Land Office (A Study of Court Decision Number 15/Pdt/2022/PT.Bdg.) - Luthfi Akmal, Muhammad; Allagan, Tiurma M. Pitta (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research discusses default in the payment of land purchase using a home ownership credit as a basis for canceling a sale that has been registered at the land office, based on the Court Decision Number 15/Pdt/2020/PT.Bdg. In this case, the bank disbursed the credit according to the credit agreement between the buyer and the bank, which should have been paid to the seller by the buyer. However, since the money was not paid despite the transfer of rights being registered at the Land Office, the seller suffered a loss due to the buyer's default. This default can create new legal problems if not promptly resolved through the court. The research method used is doctrinal legal research, based on legal doctrines and applicable laws and regulations. The research typology used is descriptive-analytical. This method describes the applicable laws and regulations and relates them to legal theories and the practice of positive law relevant to the issue. This research focuses on whether a default can annul a land sale that has been registered with the land office and the differences between default and unlawful acts in canceling an engagement based on applicable regulations. The result of this research is that the transfer of land can be annulled by proving that a default has indeed occurred through a judge's decision in accordance with Article 1266 of the Civil Code.